Korpusová analýza jazykové přesnosti v písemném projevu studentů angličtiny jako cizího jazyka. / A corpus-based analysis of EFL learners' accuracy in writing. - František Tůma (Czech Pedagogical Society, 2013)
This study presents a part of results of a research project from the field of foreign language learning and teaching, in which an analysis of a learner corpus was carried out. The research project dealt with the developing of university EFL learners' communicative competence in writing in a blended learning course. The article first briefly addresses issues related to the conceptualization of developing communicative competence and measuring learners' progress in terms of accuracy. The sample comprised 18 learners in an EFL course at the CEFR (2002) A2 level, who participated in three discussion tasks conducted online, using asynchronous discussion forums. The discussions were built on social constructivist learning theories. The main research tool was a learner corpus compiled from the texts written by the students in two online discussions. The results showed that the learners' overall level of communicative competence in writing increased. The outcomes of the corpus analysis in the field of language accuracy remain, in some respects, inconclusive. The results indicate that the learners' accuracy was linked to the communicated content. The study shows one possibility of using learner corpora in research in foreign didactics and highlights some of their imitations.